Advances in Information Retrieval 38th European Conference on IR Research, ECIR 2016, Padua, Italy, March 20-23, 2016. Proceedings - Ferro, Nicola; Crestani, Fabio; Moens, Marie-Francine; Mothe, Josiane; Silvestri, Fabrizio; Di Nunzio, Giorgio Maria; Hauff, Claudia; Silvello, Gianmaria (Information Systems and Applications, incl. Internet/Web, and HCI ;, 2016)
This book constitutes the refereed proceedings of the 38th European Conference on IR Research, ECIR 2016, held in Padua, Italy, in March 2016. The 42 full papers and 28 poster papers presented together with 3 keynote talks and 6 demonstration papers, were carefully reviewed and selected from 284 submissions. The volume contains the outcome of 4 workshops as well as 4 tutorial papers in addition. Being the premier European forum for the presentation of new research results in the field of Information Retrieval, ECIR features a wide range of topics such as: social context and news, machine learning, question answering, ranking, evaluation methodology, probalistic modeling, evaluation issues, multimedia and collaborative filtering, and many more.